Voluntary Health Insuranceas as a Tool of Employee Motivation at the Russian and Foreign Enterprises ("Journal "U". Economy. Management. Finance.", 2017)
The article considers examples of the first insurance services in the Russian Empire, Germany and the USA as prerequisites for development of voluntary health insurance (VHI) services. Comparisons of the main medical services in the Russian, German and American companies are given. Role of VHI as a tool of employee motivation from the part of employers is emphasized. Ways of achievement of the high level of employees' motivation are described in detail based on the example of a Russian enterprise.
Keywords: medical insurance; voluntary health insurance services; motivation tool